Dosimetric Verification of Intensity Modulated Radiotherapy (IMRT) Treatment Plans for Prostate Cancer Patients - Iva Mrčela; Marin Gregov; Ante Matanić; Mirjana Budanec; Jure Murgić; Blanka Jakšić; Marin Prpić; Angela Prgomet Sečan; Ana Fröbe (Acta Clinica Croatica, 2022)
Intensity modulated radiotherapy (IMRT) has become widely used as a standard radiation therapy technique for the treatment of localized prostate cancer. The transition from conformal radiotherapy (3D CRT) to a more complex IMRT technique triggered the need for more thorough verification of the accuracy in the dose delivery. In this work we present the clinical workflow and the results of patient specific quality assurance (PSQA) procedures for 40 prostate cancer patients who have been treated with step and shot IMRT ever since its implementation in our routine clinical practice. PSQA procedures include dosimetric verification of each treatment plan with dedicated rotational phantom and high-resolution matrix detector system Octavius 4D (PTW Freiburg) that allows three-dimensional comparison of the calculated and delivered radiation dose distribution. Our results proved the compliance with the universal tolerance limits recommended for those procedures (1), assuring the safety of the treatment and providing the possibility for the adoption of more stringent constraints in the future.